Macroprudential Risk Management Problems in Brexit - Paul J. J. Welfens (Intereconomics, 2018)
Brexit is not only a historical chapter of the British - EU relationship, but it also carries immense challenges for fi nancial market stability in the short and medium run for the 28 member states of the European Union. The scale of these challenges depends heavily on the outcome of EU-UK negotiations. The European Systemic Risk Board plays a critical role in macroprudential supervision, a crucial policy challenge for the EU. However, there are doubts as to whether it will fulfill its mandate. The EU27 faces major problems in terms of prudential supervision after Brexit since a very large part of their wholesale banking markets are in the UK and thus will not be regulated by the EU after 29 March 2019. Indications point to a considerable risk of a new transatlantic banking crisis in the future.
Keywords: 330; Brexit; Financial market regulation; Financial market supervision; Financial market sustainability; Stabilization policy